2003
DOI: 10.1136/ijgc-00009577-200307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, c-erbB-2, Ki-67, and CD34 in granulosa cell tumor of the ovary

Abstract: The purpose of this study is to investigate the expression of p53, c-erbB-2, Ki-67, and angiogenic activity and their correlation with the clinicopathologic characteristics in a series of granulosa cell tumors of the ovary (GCTO). Eighteen GCTO cases assisted at the Department of Obstetrics and Gynecology, School of Medical Science, UNICAMP, after diagnostic confirmation by three pathologists, were submitted to immunohistochemistry for assessment of p53, c-erbB-2, Ki-67, and CD34 expressions. The mean tumor si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…We reiterate the point that pathological review is important in such studies since some of the mimics of AGCT, such as OSCCHT, are typically diffusely p53 positive 34. Other authors have reported no prognostic significance of p53 immunohistochemical staining 5 23 24 27 28. These variations may be partly explained by differing immunohistochemical methods and scoring criteria, particularly what constitutes p53 overexpression.…”
Section: P53 Stainingmentioning
confidence: 77%
See 1 more Smart Citation
“…We reiterate the point that pathological review is important in such studies since some of the mimics of AGCT, such as OSCCHT, are typically diffusely p53 positive 34. Other authors have reported no prognostic significance of p53 immunohistochemical staining 5 23 24 27 28. These variations may be partly explained by differing immunohistochemical methods and scoring criteria, particularly what constitutes p53 overexpression.…”
Section: P53 Stainingmentioning
confidence: 77%
“…Furthermore, there was no difference in proliferation between stage I and higher stage tumours. These findings are supported by some studies,5 7 9 11 20 21 24 – 26 but are contradicted by others, that have found that a high mitotic count imparts a worse prognosis, with various cut-offs of >3 to >10 mitotic figures per 10 high-power fields 6 10 13 15 22 23 27 – 29. Some studies have found elevated Ki-67 labelling indices to adversely affect prognosis 16 28 30.…”
Section: Mitotic Activity and Ki-67 Proliferation Indexmentioning
confidence: 83%
“…Therefore it is not surprising that some reports have failed to show a correlation between mitotic activity and prognosis in patients with GCT,1623 and even those studies reporting such a correlation do not agree on the cut-off value for poor outcomes. More recent immunohistochemical investigations evaluating the expression of proliferation-associated markers such as proliferating cell nuclear antigen and Ki-67/MIB-1 have also failed to show consistent results 8 10 16 17 19 2225…”
mentioning
confidence: 98%
“…Several studies have proposed that the mitotic index of GCT is associated with tumor recurrence despite the different cutoff points of the mitotic index (7,13,16) . Meanwhile, other molecular markers do not seem to have a prognostic significance, even though angiogenic factors such as proliferating cell nuclear antigen (PCNA) and Ki-67, p-53 and abnormal tumor karyotypes have been studied for the prediction of survival (17,18) .…”
Section: Discussionmentioning
confidence: 99%